2000
DOI: 10.2139/ssrn.243226
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Ownership Structure and the Informativeness of Accounting Earnings in East Asia

Abstract: This paper was presented at the conference on Designing Financial Systems in East Asia and Japan: Toward a Twenty-First Century Paradigm. This two-day conference was co-organized by the International Monetary Fund and the CEI. It was held during September [24][25] 2001 at Hitotsubashi Memorial Hall in Tokyo, Japan. A select group of academics, researchers and policy makers from around the world gathered to examine the timely issue of how the financial systems and corporate governance in East Asia and Japan sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

91
1,037
8
49

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 644 publications
(1,185 citation statements)
references
References 43 publications
91
1,037
8
49
Order By: Relevance
“…He suggests that family members usually hold important positions on both the management team and the board of directors. These results are consistent with previous arguments which suggested that the ownership structure in East Asia companies is highly concentrated as compared to diffuse ownership structure in the US and the UK [27]. Correlation is significant at 1 percent level, 5 percent level and * 10 percent level, respectively, using two-tailed tests.…”
Section: Resultssupporting
confidence: 91%
“…He suggests that family members usually hold important positions on both the management team and the board of directors. These results are consistent with previous arguments which suggested that the ownership structure in East Asia companies is highly concentrated as compared to diffuse ownership structure in the US and the UK [27]. Correlation is significant at 1 percent level, 5 percent level and * 10 percent level, respectively, using two-tailed tests.…”
Section: Resultssupporting
confidence: 91%
“…For example, Fan and Wong (2002) and advance the hypothesis that because controlling shareholders can monitor management without public disclosures, there may be less governance-related demand for high quality financial reporting, thereby allowing controlling shareholders to protect proprietary information through less transparent reporting. Ajinkya, Bhojraj, and Sengupta (2005) (2006) test similar hypotheses and draw similar inferences when documenting that public European Union firms engage in less earnings management than private firms.…”
Section: Accounting Information and Ownership Structurementioning
confidence: 99%
“…As a result, ownership concentration and companies' earnings management activity is directly related (e.g. Choi, Jeon, & Park, 2004;Claessens, Djankov, & Lang, 2000;Fan & Wong, 2002;Kim & Yoon, 2008;Wang, 2006).…”
Section: Ownership Concentration and Earnings Managementmentioning
confidence: 99%